Child Poverty and Family Transfers in Southern Europe - Manos Matsaganis; Horacio Levy; Magda Mercader-Prats; Stefano Toso; Cathal O'Donoghue; Manuela Coromaldi; Carlos Farinha Rodrigues; Panos Tsakloglou (Institute for the Study of Labor (IZA), 2005)
The drive to reduce child poverty is of particular interest in southern Europe, where the subsidiary role of the State in matters of family policy has implied that programmes of public assistance to poor families with children are often meagre or not available at all. The paper examines the effect of family transfers (used broadly to include contributory family allowances, non-contributory child benefits and tax credits or allowances) on child poverty in Greece, Italy, Spain and Portugal. Using the European microsimulation model EUROMOD, the paper first assesses the distributional impact of existing family transfers and then explores the scope for policy reforms. By way of illustration, the effects of universal child benefit schemes similar to those in Britain, Denmark and Sweden are simulated. The paper concludes with a discussion of key findings and policy implications.
Keywords: I38; D31; C81; 330; child poverty; social transfers; fiscal benefits; south Europe; microsimulation; Kinder; Armut; Familienpolitik; Familienleistungsausgleich; Reform; Wirtschaftspolitische Wirkungsanalyse; Simulation; Griechenland; Italien; Spanien; Portugal